Composition of the aquatic birdlife of Saco da Fazenda, Itajaí-SC - Corrêa Manoel, Francine; Olinto Branco, Joaquim; Barbieri, Edison (O Mundo da Saúde, 2011)
Saco da Fazenda estuary, despite the impact caused by the flow of effluent domestic and industrial sewage coming from Itajaí-Açu River, is the shelter of a great diversity of birds. The knowledge of the composition of bird life becomes crucial in the characterization of this environment, since in threatened ecosystems, as estuaries are, we may identify alterations in biodiversity and abundance due to the influence of areas adjacent to the ecosystem. From July 2006 to April 2007 we did biweekly censuses in the assembly of birds in Saco da Fazenda. 29 species of aquatic birds, distributed in 25 genres and 13 families, being 11 of constant occurrence (37.9%), six accessory (20.6%) and 12 species of casual presence (41.3%). Grouping analysis generated through data evaluating monthly average abundance showed a “300” distance level, resulting in the formation of four distinct groups. Group I: P. brasilianus and H. himantopus, which presented the highest relative abundance. Group II: C. albus, E. thula and E. caerulea, and also G. chloropus, characterized by the abrupt reduction of units at spring end and summer beginning. A. Brasiliensis, V. chilensis and L. dominicanus integrate group III, organized due to abundances relatively next to the last two species. Group IV was composed by H. palliatus and R. niger, species with a low contribution for abundance.